Payment Cards - Liběna Kantnerová (Naše gospodarstvo/Our economy, 2016)
The aim of this paper is to analyze the use of payment cards in retail in the Czech Republic from the side of clients (buyers) and the side of sellers. Questionnaires for clients examine satisfaction with cards and the service connected with them. Sellers’ satisfaction with the profit and function of cards is analyzed. The data indicated that 92% of the 352 respondents in South Bohemia had a payment card and more than 35% had more than one card. In retail, 70% of sellers had a payment terminal.